2006
DOI: 10.1177/0022167805283779
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Existential Meaning as a Buffer Against Stress

Abstract: An ethnically diverse sample of 143 college undergraduates was used to test the hypothesis that a sense of existential meaning buffers against the effect of stress on depression and hope. Spiritual meaning as measured by the Spiritual Meaning Scale and personal meaning as measured by the framework subscale from the Life Regard Index-Revised were significantly negatively correlated with depressive symptoms and positively correlated with hope. Spiritual meaning, but not personal meaning, moderated the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 40 publications
8
85
0
7
Order By: Relevance
“…Perceived meaning of life, measured with the Meaning in Life after Cancer Scale, shows negative and significant correlations with all three variables. These results are in accordance with the literature (MASCARO & ROSEN 2004;MASCARO, ROSEN & MOREY 2006) and these relationships hold true of cancer disease (BRADY et al 1999;FIFE 1995;JIM & ANDERSEN 2007). In our study we found that results are dependent on the applied instrument measuring meaningfulness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Perceived meaning of life, measured with the Meaning in Life after Cancer Scale, shows negative and significant correlations with all three variables. These results are in accordance with the literature (MASCARO & ROSEN 2004;MASCARO, ROSEN & MOREY 2006) and these relationships hold true of cancer disease (BRADY et al 1999;FIFE 1995;JIM & ANDERSEN 2007). In our study we found that results are dependent on the applied instrument measuring meaningfulness.…”
Section: Discussionsupporting
confidence: 93%
“…According to literature, meaningfulness is related to several indicators of well-being, for example satisfaction with life, positive affectivity (ZIKA & CHAMBERLAIN 1992), self-esteem, optimism (STEGER & FRAZIER 2005), selfefficacy, subjective health (SKRABSKI et al 2005), and shows negative correlation with negative indicators of well-being, like oncological and cardiovascular mortality rates (SKRABSKI et al 2005), smoking (KONKOLŸ THEGE 2009), suicidal thoughts (EDWARDS & HOLDEN 2001), anxious and depressive symptoms (MASCARO & ROSEN 2004).…”
Section: The Relation Of Meaningfulness and Well-being Among Cancer Pmentioning
confidence: 99%
“…Decades of research have supported Frankl's main assumptions, showing MIL as an important predictor of physical health (Jim & Andersen, 2007), psychological well-being and quality of life (Fillion et al, 2009;Ho et al, 2010;Melton & Schulenberg, 2008). A lack of meaning, on the other hand, has been associated with higher depression levels (Mascaro & Rosen, 2006), suicidal ideas (Edwards & Holden, 2001), drug addiction (Henrion, 2002), among others.…”
Section: Meaning In Life and Its Relations With Health Aspectsmentioning
confidence: 97%
“…In addition, as a protective resource, MIL supports the appropriate use of coping and stress management resources, protecting subjects against negative events and feelings experienced at work (Bonebright, Clay, & Ankenmann, 2000;Mascaro & Rosen, 2006). Considering teachers as a professional group that generally displays high levels of emotional exhaustion, the aim of this study was to evaluate MIL, psychological well-being (PWB) and quality of life (QOL) rates in a comprehensive sample of school teachers, as well as to observe how MIL can act as a moderating variable of the relation between PWB and general QOL.…”
Section: Meaning In Life and Its Relations With Health Aspectsmentioning
confidence: 99%
See 1 more Smart Citation